2002
DOI: 10.1136/jech.56.7.506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of de-industrialisation on working conditions and self reported health in a sample of manufacturing workers

Abstract: Study objective: To explore the impact of de-industrialisation over a 20 year period on working conditions and health among sawmill workers, in the province of British Columbia (BC), Canada. Design and Setting: This investigation is based on a sample of 3000 sawmill workers employed in 1979 (a year before the beginning de-industrialisation) and interviewed in 1998. The sample was obtained by random selection from an already gathered cohort of approximately 28 000 BC sawmill workers. Change in working condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Spayd and Dye, 1991;Bettis, 1994), poorer health conditions (see e.g. Renner and Navarro, 1989;Wallace D. and Wallace R., 1999;Ostry et al, 2002;EIR, 2006;Holland et al, 2011), higher violence (see e.g. Ousey, 2000Matthews et al, 2001), and higher rates of both suicide (see e.g.…”
Section: The Macroeconomic Consequences Of Deindustrializationmentioning
confidence: 99%
“…Spayd and Dye, 1991;Bettis, 1994), poorer health conditions (see e.g. Renner and Navarro, 1989;Wallace D. and Wallace R., 1999;Ostry et al, 2002;EIR, 2006;Holland et al, 2011), higher violence (see e.g. Ousey, 2000Matthews et al, 2001), and higher rates of both suicide (see e.g.…”
Section: The Macroeconomic Consequences Of Deindustrializationmentioning
confidence: 99%
“…During the past decade, globalization, new technologies, and changes in workforce demographics have produced new work environments. [26][27][28] Changes in the nature of work have created workplaces demanding a level of skills and training that may also create barriers to individuals with more severe mental health problems, poor work histories, and limited qualifications.…”
Section: Possible Remediesmentioning
confidence: 99%
“…Rapidly increasing unemployment has also been associated with increased all-cause mortality rates among workers [21], and high neighbourhood unemployment rates in London (UK) have been associated with poor self-rated health [22]. A study in the British Columbia (BC) sawmill industry [23] found that workers who remained employed in sawmills during extensive restructuring were approximately 50% more likely to report poor health than those who were re-employed elsewhere. In other words, health status was better for workers who, under pressure of massive industry downsizing and change, left the sawmill industry and obtained re-employment elsewhere.…”
Section: Introductionmentioning
confidence: 99%